Trade and Credit Reallocation: How Banks Help Shape Comparative Advantage - Christian Keuschnigg; Michael Kogler (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Trade and innovation cause structural change. Productive factors must flow from declining to growing industries. Banks play a major role in cutting credit to non-viable firms in downsizing sectors and provide new credit to finance investment in expanding, innovative sectors. Structural parameters of a country's banking system thus influence comparative advantage and trade patterns. The analysis points to the importance of insolvency laws, minimum capital standards, and cost of bank equity to determine credit reallocation, sectoral expansion and trade patterns.
Keywords: F10; G21; G28; 330; Capital reallocation; banking; trade; comparative advantage